Effect of Hydrogen Sulphide on Benthic Fauna of a tropical Estuary - G., Gopakumar; V.J., Kuttyamma (Fishery Technology, 2025)
The distribution and abundance of some benthic organisms in the Kayamkulam estuary (a tropical estuary), revealed that polychaetes, tanaids, amphipods, isopods, bivalves, gastropods and nematods were the major groups of macrobenthic animals. Among these, polychaetes were the most abundant group in unpolluted area compared to hydrogen sulphide-polluted area. In the polluted area polychaetes and nematods were observed during the study period.